Terrorists and terrorism in the contemporary world - Whittaker, David J. 1925-2017 (The making of the contemporary world, 2004)
Problems in definition -- Terrorism today and yesterday -- Terrorists in groups -- Terrorists and their motivation -- Three terrorist profiles -- Tactics and methods -- Terrorists and the media -- Ethical and moral issues -- Future forms of terrorism -- Countering terrorists -- Resume and further enquiry.